Aggregation properties and toxicity of newly synthesized thiazolium based surfactants – Thermodynamic and computational study. (April 2019) - Vraneš, Milan; Petrović, Lidija; Gadžurić, Slobodan; Četojević-Simin, Dragana; Ranitović, Aleksandra; Cvetković, Dragoljub; Papović, Snežana; Tot, Aleksandar; Panić, Jovana; Milinković, Jelena
Graphical abstract: Highlights: Agregation behavior of two newly synthesized thiazolium salts are studied. Introduction of –CH3 on thiazolium ring increase thermal stability and decrease CMC. Micelle formation reduces the toxicity of salts. Additional methylation also reduces toxicity. Abstract: Two new thiazolium-based surfactants namely N -dodecylthiazolium bromide, [NddTz][Br] and N -dodecyl-4-methylthiazolium bromide, [4mNddTz][Br], were synthesized and investigated as new surface active and antimicrobial agents. Their thermal stability is determined by TG/DSC measurements, and the self-assembly behaviour in aqueous solutions systematically studied applying experimental and molecular dynamics (MD) approach. Obtained results of surface tension and electrical conductivity showed that both newly synthesized salts possess a similar surface activity in aqueous solutions compared to imidazolium-based surface active N -dodecyl-3-methylimidazolium bromide, [NddmIm][Br], ionic liquid. Also, thermodynamic parameters of micellization are calculated and compared with the results obtained by volumetric measurements. Antimicrobial activity of these salts is tested by microdilution method on Gram-positive and Gram-negative bacteria and yeasts. In vitro cytotoxicity study has been performed using human fetal lung fibroblasts (MRC-5) and colon adenocarcinoma (HT-29) cell line.